2020
DOI: 10.1007/s00167-020-06039-9
|View full text |Cite
|
Sign up to set email alerts
|

Adding corticosteroids to periarticular infiltration analgesia improves the short-term analgesic effects after total knee arthroplasty: a prospective, double-blind, randomized controlled trial

Abstract: PurposePeriarticular infiltration analgesia (PIA) is widely used to control postoperative pain in patients who underwent total knee arthroplasty (TKA). This study aimed to evaluate the efficacy of adding corticosteroids to the PIA cocktail for pain management in patients who underwent TKA. MethodsThe patients were randomized to the corticosteroid or control group (double‐blind). The patients in the corticosteroid group received a periarticular infiltration of an analgesic cocktail of ropivacaine, epinephrine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
(50 reference statements)
4
33
0
Order By: Relevance
“…There is a close relationship between postoperative pain and inflammatory response [36]. Some studies have shown that corticosteroids can alleviate pain by inhibiting inflammatory response [19,37]. However, due to the lack of relevant studies, this meta-analysis did not make detailed statistics on inflammatory indicators such as C-reactive protein, erythrocyte sedimentation rate, and IL-6.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…There is a close relationship between postoperative pain and inflammatory response [36]. Some studies have shown that corticosteroids can alleviate pain by inhibiting inflammatory response [19,37]. However, due to the lack of relevant studies, this meta-analysis did not make detailed statistics on inflammatory indicators such as C-reactive protein, erythrocyte sedimentation rate, and IL-6.…”
Section: Discussionmentioning
confidence: 92%
“…After reading the title and abstract, 199 articles were eliminated, leaving 72. Sixty-two articles were discarded for various reasons (retrospective study, review article, unicondylar knee arthroplasty, case report, intravenous injection, and expert consensus or guide) when the full text was browsed for further screening, and 10 studies [11,12,14,19,20,[22][23][24][25][26] finally met the inclusion criteria (Fig. 1, flow chart of study selection).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a close relationship between postoperative pain and in ammatory response [36]. Some studies have shown that corticosteroids can alleviate pain by inhibiting in ammatory response [20,37]. However, due to the lack of relevant studies, this meta-analysis did not make detailed statistics on in ammatory indicators such as C-reactive protein, erythrocyte sedimentation rate, IL-6.…”
Section: Discussionmentioning
confidence: 93%
“…After reading the title and abstract, 199 articles were eliminated, leaving 72. 62 articles were discarded for various reasons(retrospective study, review article, unicondylar knee arthroplasty, case report, intravenous injection and expert consensus or guide) when the full text was browsed for further screening, and 10 studies [11,12,14,[20][21][22][23][24][25][26] nally met the inclusion criteria( Figure. 1 Flow chart of study selection). The characteristics of the 10 studies involved 829 participants were summarized in Table. 1 Characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%